The effect of pregabalin on sensorimotor gating in ‘low’ gating humans and mice - Acheson, Dean T. (2012)
Pregabalin, an anticonvulsant and anxiolytic compound that binds to α2-δ auxiliary subunit Types 1 and 2 of voltage-gated calcium channels, has been shown to reduce excitatory neurotransmission partially through modulation of glutamatergic signaling. Prepulse inhibition (PPI) of startle is an operational measure of sensorimotor gating impacted by disruption of the glutamatergic system and is reduced in schizophrenia patients. Dysregulation of the glutamatergic system has also been implicated in the pathophysiology of schizophrenia. Here we tested the hypothesis that pregabalin may ameliorate PPI in a model of deficient gating in humans and mice. In study 1, 14 healthy human subjects participated in a within subjects, cross-over study with placebo, 50 mg or 200 mg pregabalin treatment prior to undergoing a PPI task. In study 2, 24 C57BL/6 mice underwent a similar procedure with vehicle, 30 and 100 mg/kg dose treatments. In both studies, subjects were assigned to a “Low” or “High” gating group using a median split procedure based on their PPI performance during placebo/vehicle. Drug effects were then examined across these groups. In humans, pregabalin treatment significantly increased PPI performance in the “low gating” group. In mice, pregabalin treatment significantly increased PPI in the low gating group but reduced PPI in the high gating group. Across species, pregabalin treatment improves PPI in subjects with low gating. These data support further exploration of pregabalin as a potential treatment for disorders characterized by sensorimotor gating deficits and glutamatergic hypersignaling, such as schizophrenia.